Add on testosterone therapy in negative symptoms of schizophrenia with gonadal trauma: Hitting the bull's eye. (30th June 2016) - Jha, Shailesh; Garg, Amit
Abstract: The coincidence or causal incidence of hormonal dysregulation leading to psychotic manifestation had been a point of debate. The interplay of these hormones in pathogenesis of psychotic symptom domains is still inconclusive along with some symptom domains which worsen with antipsychotics. Early detection and treatment with liaison approach is of great help to such patients. We report a case of schizophrenia with primary hypogonadism that responded dramatically to add on testosterone supplement. Highlights: Negative symptom domains of schizophrenia relates with low testosterone level. Preexisting hypogonadism in such cases complicates the presentation and management. Debate regarding coincidence vs causal incidence remains inconclusive. Add on testosterone therapy has good response to ongoing risperidone therapy.